1997
DOI: 10.1099/00221287-143-7-2267
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the inducible acetamidase gene of Mycobacterium smegmatis

Abstract: The inducible acetamidase of Mycobacterium smegmatis NCTC 81 59 is expressed at high levels in the presence of a suitable inducer, such as acetamide. The gene and 1.5 kb of upstream sequence had previously been sequenced. A further 14 kb of upstream sequence has now been determined, containing an additional ORF on the opposite strand to the acetamidase gene. This ORF has significant homologies to genes encoding regulatory proteins involved in amidase expression in other organisms. Restriction fragments from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
131
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(138 citation statements)
references
References 29 publications
7
131
0
Order By: Relevance
“…We reasoned that one approach to understand the function of MtrA would be to elevate its intracellular levels in M. tuberculosis and evaluate the consequences associated with elevated protein levels on the growth of the virulent M. tuberculosis strain under different conditions. We chose Mycobacterium smegmatis -derived inducible amidase promoter to elevate the intracellular levels of MtrA (Parish et al ., 1997;Triccas et al ., 1998). Our preliminary experiments revealed that this promoter was constitutively active in M. tuberculosis (data not shown).…”
Section: Mtra Levelsmentioning
confidence: 99%
“…We reasoned that one approach to understand the function of MtrA would be to elevate its intracellular levels in M. tuberculosis and evaluate the consequences associated with elevated protein levels on the growth of the virulent M. tuberculosis strain under different conditions. We chose Mycobacterium smegmatis -derived inducible amidase promoter to elevate the intracellular levels of MtrA (Parish et al ., 1997;Triccas et al ., 1998). Our preliminary experiments revealed that this promoter was constitutively active in M. tuberculosis (data not shown).…”
Section: Mtra Levelsmentioning
confidence: 99%
“…This vector was further modified by replacing hsp60 promoter cassette with an ϳ2.6-kb PCR-amplified upstream region of formamidase gene from M. smegmatis to yield pMV261Acet vector (kindly provided by Manika I. Singh, IISER Bhopal). This cloning, although followed by the published method (30), will be detailed elsewhere. This vector has been utilized for the expression of all the constructs in M. smegmatis upon induction by acetamide; acetamide-mediated induction has been shown to be very useful for the controlled expression of proteins in mycobacteria (31,32).…”
Section: Methodsmentioning
confidence: 99%
“…To confirm that SigH is phosphorylated in M. tuberculosis containing native levels of PknB, we made a strain in which M. tuberculosis sigH fused to the FLAG epitope sequence at the carboxyl-terminus was expressed under the control of the inducible acetamidase promoter (15,16). Total protein was extracted from this sigH-FLAG-expressing strain, separated by 2D GE, immunoblotted with anti-FLAG antibody, stripped, and then reprobed with phospho-T specific antibody.…”
Section: In Vivo and In Vitro Phosphorylation Of Sigh And Identificatmentioning
confidence: 99%
“…To determine whether RshA is phosphorylated in vivo in M. tuberculosis, we made an M. tuberculosis strain in which M. tuberculosis rshA fused to the FLAG epitope tag sequence was expressed under the control of the inducible acetamidase promoter (15,16). Total protein was extracted from this rshA-FLAG-expressing strain, separated by 2D GE using a linear pI range 5-8 isoelectric focusing (IEF) strip, and immunoblotted with anti-FLAG antibody.…”
Section: In Vivo and In Vitro Phosphorylation Of Rsha And Identificatmentioning
confidence: 99%
See 1 more Smart Citation